MEMBANGUN SPIRIT KEWIRAUSAHAAN SEBAGAI LANGKAH POSITIF DI MASA PANDEMI PADA KELOMPOK PKK KEL. CIPINANG MELAYU - Muger Apriansyah; Sahroni Sahroni; Moh. Sutoro; Mukrodi Mukrodi; Edy Krisyanto (LPPM Universitas Pamulang, 2020)
This community service aims to foster entrepreneurship spirit the pandemic situation in PKK Kel. Cipinang Melayu group. As the things Issues raised how to start a business with good managemen. The method used in the implementation of this service is carried out in several activities, namely (a). The Preparation Phase includes: (1). Initial survey (2) Consolidation and determination of target locations, (3). Preparation to sosialitations of materials / materials. The results of this activity can later be beneficial for to PKK Kel. Cipinang Melayu group, in starting entrepreneurship with a good mangement approach in a pandemic situation.Keywords: Entrepreneur, Business Management, Business Independence, Pandemic